(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses aspects of the spiritual heritage of Khoja Akhrar Vali associated with the great mystic Abu Said Abul Khair (d. 440/1048), the founder of the Khorasan school of mysticism. “Risalai Khavroya” (“Treatise on Khurrah”) by Khoja Ahrar Vali is devoted to the analysis of the rubaiyat written by Abu Said Abul Khair, which was considered favorable when reading to a sick person and therefore was commented on by many people.